Architectural Drawing in the Escuela de Madrid during the 1960s (diségno, 2018)
This article is intended to provide a sample of the architectural drawing undertaken by Spanish architects of the so-called ‘Madrid School’ in the 1960s. During that decade, a good number of architects were prominent within what came to be known as the ‘modern organic style’. This comprised works strongly rooted in the places where they were built and of considerable construction quality, thanks to the use of traditional materials. The article also has an objective on the theory front. In contrast with the relativism of criteria for evaluating art, it claims that it is possible to speak of a ‘canon of excellence’. The basis is a rigorous selection of the architects with the highest profiles in the years under consideration. This would rate drawings as of greater or lesser relevance, and see means of representing architecture as of more or of less significance at a given point in historical time.
Keywords: Architectural Drawing; Spain; 1960-1969